Waste Management And Separation Education Organic And Inorganic Manufacturing And Place Waste From Bamboo - Rena Rahmawati; Refi Lestari Castriani; Pasya Afnuria (Fakultas Kewirausahaan Universitas Garut, 2021)
AbstractThe surabaya village is a village situated in Surabaya, the Balubur Limbangan subdistrict, the Garut district, west Java province. The village of 2 Surabaya was a prosperous village with the majority of its population's livelihoods including creations as caged and clay-grids. The awareness and care to handle the waste by peasant people 2 seemed to be lacking. The habit of burning garbage still runs deep in the peasant community to deal with the garbage problem. Besides, burning up human garbage is the quickest way to address the problem. As well as the garbage control approach to children through the practice of garbage makes them happy that there is something they can make from the garbage at their own pace and the hope of their future creativity can be spoiled in dealing with the problem of garbage and the presence of kader environmental in their village Abstrak Dusun 2 Surabaya merupakan dusun yang terletak di Desa Surabaya, Kecamatan Balubur Limbangan, Kabupaten Garut, Provinsi Jawa Barat. Dusun 2 Surabayamerupakan desa yang makmur dengan mayoritas mata pencaharian penduduknya meliputi kreasi sebagai pengrajin sangkar dan cobek dari tanah liat. Kesadaran dan kepedulian untuk menangani sampah oleh masyarakat dusun 2 terlihat masih sangat kurang. Kebiasaan membakar sampah masih mendarah daging di masyarakat dusun dalam menangani permasalahan sampah. Disamping itu dengan membakar sampah dirasa masyarakat adalah cara yang paling cepat dalam menangani permasalahan tersebut. Serta pendekatan pengendalian sampah kepada anak-anak melalui kegiatan pembuatan prakarya dari sampah membuat mereka senang karena ada sesuatu yang dapat mereka buat dari sampah dengan usaha mereka sendiri dan harapannya kreatifitas mereka kedepannya dapat terasah dalam menangani masalah sampah dan muncul kaderkader peduli lingkungan di dusun mereka